The Impact of Inflammatory Bowel Disease in Canada 2018: Extra-intestinal Diseases in IBD - Bernstein, Charles N (J Can Assoc Gastroenterol, 2019)
The burden of extra-intestinal disease is high in patients with IBD, some of whom respond to or are prevented by treating the bowel inflammation, whereas others require specific treatment because they are independent of the underlying bowel inflammation. Among the most common extra-intestinal manifestations are other chronic immune-mediated diseases such as erythema nodosum, ankylosing spondylitis and primary sclerosing cholangitis. Patients with IBD are at higher risk of complications in other organ systems such as osteoporosis, venous thromboembolism and cardiovascular disease. In addition, patients with IBD have a higher risk of cancer, including colon cancer. Mental health comorbidity is important and common in IBD though not always recognized and managed. Consequently, patients and care providers need to be vigilant in the surveillance of extra-intestinal manifestations and complications of IBD. HIGHLIGHTS: 1. The burden of extra-intestinal disease is high in patients with IBD. 2. Immune-mediated inflammatory diseases (IMIDs) commonly coexist with patients with IBD and the activity of IMIDs can be either dependent or independent of bowel inflammation. 3. Patients with IBD can be diagnosed with coexisting diseases that affect every organ, including bones, blood, heart, liver, and others. 4. Patients with IBD are at increased risk of cancer, including colon cancer, caused by their bowel inflammation, cholangiocarcinoma due to primary sclerosing cholangitis, and rarely lymphoma related to immunosuppressive medications. 5. The best way to prevent or reduce the burden of many of the extra-intestinal disease is to treat the inflammation of IBD, however some extra-intestinal inflammatory diseases run courses that are independent of the intestinal disease activity. KEY SUMMARY POINTS: 1. Patients with IBD are often burdened with extra-intestinal manifestations, some of which respond to or are prevented by treating the bowel inflammation whereas others require specific treatment because they are independent of the underlying bowel inflammation. 2. Other immune-mediated inflammatory diseases (IMIDs) can coexist with IBD. 3. Some IMIDs run an independent course from the bowel inflammation of IBD, such as ankylosing spondylitis, iritis, and primary sclerosing cholangitis. 4. Immune-mediated inflammatory diseases that often have courses that match the bowel inflammation of IBD include erythema nodosum and peripheral arthritis. 5. Immune-mediated inflammatory diseases such as multiple sclerosis and psoriasis have been associated with IBD. However, these conditions may also emerge as complications of therapy for IBD. 6. Patients with IBD are at risk for venous thromboembolic disease, which occurs at a rate of one per 200 person-years. 7. Venous thromboembolic disease can be reduced by treating patients admitted to hospital with an IBD diagnosis with venous thromboembolism prophylaxis. 8. Arterial vascular disease is also increased in IBD patients, including both coronary artery disease and cerebrovascular disease. 9. Osteoporosis is more prevalent in IBD patients and translates to a 40% increased risk of fracture. While corticosteroids increase the risk of osteoporosis, patients with IBD can also develop metabolic bone disease independent of corticosteroid use. 10. Persons with IBD are more likely to be infected with Clostridium difficile than community controls and often without prior antibiotic exposure. 11. Mental health comorbidity is important in IBD. Depression may antedate a diagnosis of IBD by several years and increase post-diagnosis. High stress can exacerbate symptoms in IBD but does not necessarily increase bowel inflammation. 12. Fatigue is a common symptom in IBD and is not always explained by depression, active inflammatory disease or other apparent factors. 13. The risk of colorectal cancer is increased twofold in Crohn’s colitis and in ulcerative colitis and 10-fold in persons with primary sclerosing cholangitis with colitis. 14. Primary sclerosing cholangitis runs a course independent of IBD and can progress to cirrhosis, liver transplantation or death. Patients with IBD and primary sclerosing cholangitis are at higher risk of cholangiocarcinoma, which is often fatal. 15. The risk of lymphoma may be increased in older males with Crohn’s disease and in patients using thiopurines or anti-TNF therapy. 16. The risk for intensive care unit admission is nearly twofold higher for patients with IBD and higher in Crohn’s disease than in ulcerative colitis. Risk factors for intensive care unit admission from the year before admission included cumulative corticosteroid use and IBD-related surgery. GAPS IN KNOWLEDGE AND FUTURE DIRECTIONS: 1. Patients with IBD are often burdened with extra-intestinal disease. Future research should determine the collective frequency and added costs of living with extra-intestinal disease. 2. Immune-mediated inflammatory diseases are commonly codiagnosed with IBD. Future research should focus on the pathogenesis connecting coexisting IMIDs with IBD. 3. Care pathways that support the investigation and mitigation of extra-intestinal disease are needed. For example, when and how ambulatory patients with IBD should receive prophylaxis against venous thromboembolic disease is unknown. 4. With an aging IBD population, the burden of extra-intestinal disease should be studied in the context of comorbidities of advancing age. 5. Increasing mental health screening and access to mental health care should be a goal of IBD management.